Interaction of tantalum with gases - Pylypenko, M.M.; Drobyshevskaya, A.A. (Физическая инженерия поверхности, 2014)
Kinetics of tantalum degassing by vacuum extraction of gases of heated metal in temperature range 1675—2275 K is studied. Main component of the gases that separated from metal is nitrogen. The dependence for determination of the residual content of nitrogen in degassed tantalum is obtained. It was established that during heating in the temperature range 1825—1875 K tantalum maximally absorbs oxygen and nitrogen. Вакуумной экстракцией газов нагретого металла в диапазоне температур 1675—2275 К изучена кинетика дегазации тантала. Основной составляющей выделившихся газов является азот. Получены закономерности, позволяющие определить остаточное содержание азота в дегазируемом тантале. Установлено, что при нагреве тантала в температурном интервале 1825 — 1875 К происходит максимальное поглощение танталом азота и кислорода. Вакуумною екстракцією газів нагрітого металу в діапазоні температур 1675—2275 К вивчена кінетика дегазації танталу. Основною складовою газів, що виділилися, є азот. Отримані закономірності, що дозволяють визначити залишковий вміст азоту в танталі, що дегазується. Встановлено, що при нагріванні танталу в температурному інтервалі 1825—1875 К відбувається максимальне поглинання танталом азоту і кисню.